ONLINE EVENT MANAGEMENT SYSTEM (International Journal of Food and Nutritional Sciences, 2024)
The Online Event Management System Project in PHP provides a comprehensive solution for efficiently managing events. With its user-friendly interface and robust features, this system helps streamline event management, ensuring successful and memorable experiences for all stakeholders involved.The system allows organizers to manage resources and vendors associated with events. This includes booking venues, arranging equipment, and coordinating with external service providers such as caterers or decorators. The system facilitates seamless communication between organizers, participants, and vendors. Comprehensive reports and analytics provide event organizers with insights into event performance. The Event Management System is developed using PHP as the server-side scripting language. It incorporates HTML, CSS, and JavaScript for the user interface and interactivity. MySQL or another relational database is used for data storage and retrieval.